The debt-free spending plan eaudiobook An amazingly simple way to take control of your finances once and for all. - Nagler, JoAnneh (Ascent Audio, 2012)
Anyone suffering under the crushing weight of debt knows how impossible it can seem to find a way out. It's overwhelming - and the more complicated the proposed solution, the harder it is to stick with it. That's why "The Debt-Free Spending Plan" is simple. It doesn't require sifting through chapters of high-minded financial advice or digging up your past spending history. It assumes you need help right now, and gives it to you. You will learn to: downsize expenses without feeling deprived; allocate money as it comes in and put together an easy-to-manage bill-paying plan; adjust for inevitable overspending; and, pay off debt without gouging expenses and (believe it or not) start saving. The plan is clear, easy, and takes just five minutes a day-and it doesn't matter if you make $14,000 or $14 million. With straightforward daily spending strategies and effortless expense tracking tools, you will soon find yourself on the road to financial freedom-all before the next billing cycle.